2014
DOI: 10.1002/mds.25863
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and risk of Parkinson's disease: A meta‐analysis of observational studies

Abstract: Alcohol intake, especially beer, might be inversely associated with risk of Parkinson's disease

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 41 publications
5
62
1
Order By: Relevance
“…The association of alcohol intake and the risk of Parkinson's disease has been the subject of one meta‐analysis and one review paper . The meta‐analysis of 32 studies (eight prospective cohort, 17 matched case‐control, and seven unmatched case‐control studies) found that alcohol intake could be associated with reduced Parkinson's disease risk, with a stronger association found in studies performed in Europe compared to studies from the United States and Asia . In another meta‐analysis, a weak protective association tended to be reported in case‐control studies rather than prospective cohort studies .…”
Section: Analytical Epidemiologymentioning
confidence: 99%
“…The association of alcohol intake and the risk of Parkinson's disease has been the subject of one meta‐analysis and one review paper . The meta‐analysis of 32 studies (eight prospective cohort, 17 matched case‐control, and seven unmatched case‐control studies) found that alcohol intake could be associated with reduced Parkinson's disease risk, with a stronger association found in studies performed in Europe compared to studies from the United States and Asia . In another meta‐analysis, a weak protective association tended to be reported in case‐control studies rather than prospective cohort studies .…”
Section: Analytical Epidemiologymentioning
confidence: 99%
“…A similar inverse association was seen in a Swedish case-control questionnaire study between meat consumption (broiled or smoked) and PD risk (179). While wine, liquor and alcohol in general have inconsistently or modestly been associated to a lower likelihood of PD (180), beer, which is rich in purines and can increase urate (181, 182), has a stronger link to a reduced risk of PD in some (183, 184) but not all studies (185). …”
Section: Dietary Determinants Of Pdmentioning
confidence: 99%
“…It has been argued that reduced striatal dopaminergic signalling may cause these personality traits. There is also evidence that PD patients engage in less addictive behaviours than the general population, such as smoking, alcohol and caffeine use, which may or may not be secondary to these personality differences [4], [5]. Conversely, a significant proportion of patients can develop impulsive-compulsive behaviours (ICB) when treated with dopamine agonists [6].…”
Section: Introductionmentioning
confidence: 99%